1992
DOI: 10.1002/jlb.52.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of apoptotic neutrophils does not induce macrophage release of thromboxane B2

Abstract: Senescent human neutrophils undergo programmed cell death (apoptosis), leading to their recognition and phagocytosis by mature macrophages. At inflamed sites in vivo these processes may represent a neutrophil removal mechanism with the potential to limit the histotoxic capacity of these cells. Phagocytosis can provoke marked proinflammatory responses by macrophages. A macrophage proinflammatory response to the ingestion of apoptotic neutrophils would limit the efficacy of this neutrophil removal mechanism as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
162
0
5

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 271 publications
(175 citation statements)
references
References 16 publications
8
162
0
5
Order By: Relevance
“…Another relevant observation from the apoptotic neutrophil field is that the normal noninflammatory clearance mechanisms of macrophages can be subverted by concomitant engagement of Fc receptors (32). Coating of MSU crystals with IgG may thus predispose certain individuals to a more proinflammatory reaction to crystal deposition in their joints.…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant observation from the apoptotic neutrophil field is that the normal noninflammatory clearance mechanisms of macrophages can be subverted by concomitant engagement of Fc receptors (32). Coating of MSU crystals with IgG may thus predispose certain individuals to a more proinflammatory reaction to crystal deposition in their joints.…”
Section: Discussionmentioning
confidence: 99%
“…We noted that AMT covered mouse corneas show rapid resolution of corneal inflammation consistent with rapid reduction of PMN (Heiligenhaus et al, 2001). Previously, it has been suggested that apoptosis of PMN is a new strategy to clear a large number of PMN and their potentially histotoxic contents to achieve rapid resolution of acute inflammation (Meagher et al, 1992;Stern et al, 1996). Therefore, we re-examined this mouse model of HSK-induced necrotizing keratitis and investigated the mechanism explaining the fate of PMN after AMT.…”
Section: Introductionmentioning
confidence: 99%
“…When neutrophils die by apoptosis they retain their granule contents but lose chemotactic and secretory responsiveness [8] and thereafter are recognised and phagocytosed intact by macrophages [9] which fail to release pro-inflammatory mediators in response to this interaction [10]. Although neutrophils un-*Corresponding author.…”
Section: Introductionmentioning
confidence: 99%